General anesthesia of endhotracheal tube in cholesistektomy with cholelithiasis with cholecystitis: A case report - Prayoga Esa Dahan; Suandika Made; Jerau Emiliani Elsi; Indriani (BIO Web of Conferences)
Gallstones can develop in cholelithiasis, a disorder that causes inflammation and symptoms include pain in the upper right abdomen. According to this study, a 33-year-old lady has experienced periodic nausea and recurrent upper right abdomen pain for a number of years. Data for a descriptive case study were gathered by closely observing and tracking hemodynamic reactions while under anesthesia. Laboratory testing, ultrasonography, and a physical examination were used to confirm the diagnosis of cholelithiasis. Under general anesthesia and endotracheal intubation, the patient had a cholecystectomy. In addition to fentanyl for analgesia, pre-anesthesia preparation contained ondansetron and atropine to prevent bradycardia and nausea. Fentanyl, propofol, and rocuronium were used for induction, while fentanyl, ibuprofen, and vitamin C were used for postoperative pain control. With the proper anesthetic modifications, the patient stayed steady throughout the procedure. Tramadol and a heated blanket were used to treat postoperative shivering, whereas 3% sevoflurane was used to preserve consciousness. The patient was prepared for transfer to the inpatient ward, as indicated by their aldrete score of 9. This study finds that endotracheal intubation combined with general anesthesia works well for cholecystectomy in individuals with cholelithiasis. A multimodal approach to pain and shivering control, along with proper anesthetic management, guarantees hemodynamic stability, reduces discomfort, and promotes a quicker recovery.